A Cross-Cultural Perspective Of Supervisory Values - Peterson, Richard B. (Academy of Management Journal, 1972)
This paper reports on the results of a study of the attitudes of international chief executives toward supervisory values and practices. As such, this paper is part of a larger study of the attitudes of international chief executives toward education and management education, business responsibility, and labor-management relations and supervision. Questionnaires were set to 571 top executives throughout the world to test the role of culture in explaining the attitudinal responses of the responding population. Usable replies were received from 177 top executives (or 31 percent of the sample chosen). Statistically significant differences were found for the five cultural groupings in five of the eight questions dealing with supervisory values and practices. Furthermore, the confidence level was greater than 0.001 in four of the five significant questions. The results were also tested with other demographic characteristics. Only in the cases of (a) ownership of firm by chief executive, and (b) size of company were there significant differences in at least one-half of the questions. The results of the analysis of variance tests supported the hypothesis that culture plays an important role in explaining the differences in attitudinal responses by the chief executives. The value of the findings rests with the need of international firms to recognize the limitations of any universal managerial philosophy at the present time.